Deep Ocean Mineral Supplementation Enhances the Cerebral Hemodynamic Response during Exercise and Decreases Inflammation Postexercise in Men at Two Age Levels - Wei, Ching-Yin; Chen, Chung-Yu; Liao, Yi-Hung; Tsai, Yung-Shen; Huang, Chih-Yang; Chaunchaiyakul, Rungchai; Higgins, Matthew F.; Kuo, Chia-Hua (Frontiers in Physiology, 2017)
Background: Previous studies have consistently shown that oral supplementation of deep ocean minerals (DOM) improves vascular function in animals and enhances muscle power output in exercising humans. Purpose: To examine the effects of DOM supplementation on the cerebral hemodynamic response during physical exertion in young and middle-aged men. Design: Double-blind placebo-controlled crossover studies were conducted in young (N=12, aged 21.2±0.4 y) and middle-aged men (N=9, aged 46.8±1.4 y). The counter-balanced trials of DOM and Placebo were separated by a two-week washout period. DOM and Placebo were orally supplemented in drinks before, during, and after cycling exercise. DOM comprises desalinated minerals and trace elements from seawater collected 618 meter below earth surface. Methods: Cerebral hemodynamic response (tissue hemoglobin) was measured during cycling at 75% VO2max using near infrared spectroscopy (NIRS). Results: Cycling time to exhaustion at 75% VO2max and the associated plasma lactate response were similar between the Placebo and DOM trials for both age groups. In contrast, DOM significantly elevated cerebral hemoglobin levels in young men and, to a greater extent, in middle-aged men compared with Placebo. An increased neutrophil to lymphocyte ratio (NLR) was observed in middle-aged men, 2 h after exhaustive cycling, but was attenuated by DOM. Conclusion: Our data suggest that minerals and trace elements from deep oceans possess great promise in developing energy supplements to increase the cerebral hemodynamic response against physical challenge and post-exercise recovery for middle-aged men. Keywords: rehydration, minerals, trace elements, muscle power, inflammation, aging